2014
DOI: 10.1007/s10441-014-9234-8
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Analysis of a Chlamydia Epidemic Model with Pulse Vaccination Strategy

Abstract: In this paper, we have considered a dynamical model of Chlamydia disease with varying total population size, bilinear incidence rate and pulse vaccination strategy. We have defined two positive numbers R₀ and (R₁≤ R₀). It is proved that there exists an infection-free periodic solution which is globally attractive if R₀ < 1 and the disease is permanent if R₁> 1 The important mathematical findings for the dynamical behaviour of the Chlamydia disease model are also numerically verified using MATLAB. Finally epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Studies analyzing mathematical models for STDs addressing important epidemiological implications have been reported [15][16][17][18][19]. Mathematical models could provide additional insights in disease epidemiology with the ultimate goal of formulating preventive measures for halting the rise in sexually transmitted infections.…”
Section: Adolescent Pregnancy and Risks For Congenital Syphilismentioning
confidence: 99%
“…Studies analyzing mathematical models for STDs addressing important epidemiological implications have been reported [15][16][17][18][19]. Mathematical models could provide additional insights in disease epidemiology with the ultimate goal of formulating preventive measures for halting the rise in sexually transmitted infections.…”
Section: Adolescent Pregnancy and Risks For Congenital Syphilismentioning
confidence: 99%
“…They showed that stratifying the Chlamydia trachomatis model, based on the risk of acquiring or transmitting infection, induced the phenomenon of backward bifurcation even when the re-infection of recovered individuals did not occur. Samanta [32] developed a mathematical model for Chlamydia with pulse vacciantion strategy. He showed using simulations with MATLAB, the conditions under which the disease will go into extinction and when the disease will persist in the population.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models have become important tools in studying the behaviour of infectious diseases [14,15,16,17,18,19,20,21,22,23]. Mathematical models have also been developed to understand the dynamics of Chlamydia trachomatis, gonorrhea or their co-infections [24,25,26,27,28,29,30]. For instance, Gkana and Zachilas [24] developed a deterministic epidemic model for the spread of gonorrhea.…”
Section: Introductionmentioning
confidence: 99%